Energetics of male field-sport athletes during the 3-min all-out test for linear and shuttle-based running - Kramer, M.; Du Randt, R.; Watson, M.; Pettitt, R. W. (European Journal of Applied Physiology, 2019)
Purpose: All-out, non-steady state running makes for difficult comparisons regarding linear and shuttle running; yet such differences remain an important distinction for field-based sports. The purpose of the study was to determine whether an energetic approach could be used to differentiate all-out linear from shuttle running. Methods: Fifteen male field-sport athletes volunteered for the study (means ± SD): age, 21.53 ± 2.23 years; height, 1.78 ± 0.68 m; weight, 83.85 ± 11.73 kg. Athletes completed a graded exercise test, a 3-min linear all-out test and two all-out shuttle tests of varied distances (25 m and 50 m shuttles). Results: Significant differences between the all-out tests were found for critical speed (CS) [F(8.97), p < 0.001), D' (finite capacity for running speeds exceeding critical speed) [F(7.83), p = 0.001], total distance covered [F(85.31), p < 0.001], peak energetic cost (EC) [F(45.60), p < 0.001], peak metabolic power (P) [F(23.36), p < 0.001], average EC [F(548.74), p < 0.001], maximal speed [F(22.87), p < 0.001] and fatigue index [F(3.93), p = 0.027]. Non-significant differences were evident for average P [F(2.47), p = 0.097], total EC [F(0.86), p = 0.416] and total P [F(2.11), p = 0.134]. Conclusions: The energetic approach provides insights into performance characteristics that differentiate linear from shuttle running, yet surprising similarities between tests were evident. Key parameters from all-out linear and shuttle running appear to be partly interchangeable between tests, indicating that the final choice between linear and shuttle testing should be based on the requirements of the sport.